2009
DOI: 10.1118/1.3259739
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐source spiral CT with pitch up to 3.2 and 75 ms temporal resolution: Image reconstruction and assessment of image quality

Abstract: A high-pitch (up to pitch = 3.2), high-temporal-resolution (up to 75 ms) dual-source CT scan mode produced equivalent image quality relative to single-source scans using a more typical pitch value (pitch = 1.0). The resultant reduction in the overall acquisition time may offer clinical advantage for cardiovascular, trauma, and pediatric CT applications. In addition, ECG-triggered high-pitch scanning may be useful as an alternative to ECG-triggered sequential scanning for patients with low to moderate heart rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
114
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(118 citation statements)
references
References 39 publications
2
114
0
2
Order By: Relevance
“…In addition, the high sensitivity of the pediatric population to radiation and the cumulative radiation dose in critically ill children require careful handling with this technique [21,22]. Prospectively ECG-triggered high-pitch spiral mode accounts for most effective radiation dose and allows for the examination of the whole heart within a single heartbeat [23][24][25][26]. The feasibility and accuracy of high-pitch CT imaging in children with congenital heart disease has been demonstrated by Han et al [20].…”
Section: Introductionmentioning
confidence: 97%
“…In addition, the high sensitivity of the pediatric population to radiation and the cumulative radiation dose in critically ill children require careful handling with this technique [21,22]. Prospectively ECG-triggered high-pitch spiral mode accounts for most effective radiation dose and allows for the examination of the whole heart within a single heartbeat [23][24][25][26]. The feasibility and accuracy of high-pitch CT imaging in children with congenital heart disease has been demonstrated by Han et al [20].…”
Section: Introductionmentioning
confidence: 97%
“…Flohr et al [12] reported a theoretical TR value for the DHM at a high pitch factor of 3.2 for a 128-slice DSCT scanner. Our measurements indicated that the maximum TR value of the DHM was 0.074 s (R = 0.285 s; P = 3.2).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we analysed the TR and TSP shape of a modern CT scanner, such as a dual source CT (DSCT) scanner [12] and an area detector CT (ADCT) scanner [13] using the impulse method and assessed the actual maximum TR for particular helical acquisition modes.…”
Section: Introductionmentioning
confidence: 99%
“…The whole heart is completely scanned within one heart cycle, that is, the topmost image will be acquired at the set trigger point and subsequent images display the heart in later phases of the heart cycle [8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%